A multichannel optical computing architecture for advanced machine vision - Zhihao Xu; Xiaoyun Yuan; Tiankuang Zhou; Lu Fang (Light: Science & Applications, 2022)
We develop Monet: a multichannel optical neural network architecture for a universal multiple-input multiple-channel optical computing based on a novel projection-interference-prediction framework, solving real-world advanced machine vision tasks optically.